Elementy verbalnoj magii v rossijskom oficioznom diskurse - Vasilev Dmitrijevič, Aleksandr (Wydawnictwo Naukowe UAM, 2013)
The article is dedicated to phenomena of verbal magic, which exploit in modern Russian semi-official discourse for the purpose of social consciousness’ manipulation.
The Elements of Verbal Magic in Russian Semi-Official Discourse
Keywords: verbal magic; Russian semi-official discourse; political language; police terror; indoctrination